IMPLEMENTASI PROGRAM KAWASAN RUMAH PANGAN LESTARI DI KOTA SEMARANG: POTENSI EKONOMI YANG PERLU DITUMBUHKAN - Kusumaningsih, Erma; Tyas, Wido Prananing (Magister Pembangunan Wilayah dan Kota,Undip, 2019)
This study is intended to determine the extent of the implementation of the KRPL program in Semarang city, with a focus on analyzing the characteristics of its implementation and analyzing the program's contribution to the economies of beneficiary families. This study uses a mixed method that elaborates quantitative and qualitative analysis. Quantitative analysis was carried out through a survey method by distributing questionnaires to all members of the household beneficiaries in 2018, totaling 120 people. Qualitative analysis was used to strengthen quantitative analysis, through in-depth interviews with Semarang Food Security Department officials and companion group of beneficiaries.Â The results showed that the characteristics of the KRPL program beneficiaries were mostly productive age housewives with primary and secondary education. The implementation of the KRPL program has the potential to grow economic benefits. Even though at present, the KRPL program is limited to self-consumption and contributes to reducing domestic expenditure on food, but if taken seriously and sustainably on a broader scale, this program can be an alternative to improve welfare and reduce urban poverty